2003
DOI: 10.1074/jbc.m210037200
|View full text |Cite
|
Sign up to set email alerts
|

Growth Differentiation Factor-15 Prevents Low Potassium-induced Cell Death of Cerebellar Granule Neurons by Differential Regulation of Akt and ERK Pathways

Abstract: Growth differentiation factor-15 (GDF-15) is a novel member of the transforming growth factor-␤ superfamily and has been shown to be induced in neurons subsequent to lesions. We have therefore begun to study its putative role in the regulation of neuron survival and apoptosis. Cultured cerebellar granule neurons (CGN) survive when maintained in high K ؉ (25 mM) but undergo apoptosis when switched to low K ؉ (5 mM). GDF-15 prevented death of CGN in low K ؉ . This effect could be blocked by phosphatidylinositol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
95
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(106 citation statements)
references
References 88 publications
10
95
0
1
Order By: Relevance
“…We found that PDF seems to act primarily through the PI3K/Akt pathway. This finding is consistent with reports from other groups showing that PDF can activate the PI3K/Akt pathway (43,44). Additionally, PDF has recently been shown to transactivate the ErbB2 receptor, which could subsequently activate the PI3K pathway (25).…”
Section: Discussionsupporting
confidence: 93%
“…We found that PDF seems to act primarily through the PI3K/Akt pathway. This finding is consistent with reports from other groups showing that PDF can activate the PI3K/Akt pathway (43,44). Additionally, PDF has recently been shown to transactivate the ErbB2 receptor, which could subsequently activate the PI3K pathway (25).…”
Section: Discussionsupporting
confidence: 93%
“…The intensity of the staining was quantified according to Gregory. 27 granule neurons via the PI3K/Akt pathway 53 or induces apoptosis and inhibits the proliferation of several tumor cell lines. 54 Interestingly, the two MGUS BMMSCs located in the 'myeloma cluster' on genetic profiling secreted twice more GDF15 than the three MGUS BMMSCs located in the 'normal cluster'.…”
Section: Discussionmentioning
confidence: 99%
“…CGNs were isolated and cultured from 8-d-old Wistar rats as described previously (Subramaniam et al, 2003). Cells were resuspended in high K ϩ [Eagle's basal medium containing 10% fetal calf serum, 25 mM KCl, 2 mM glutamine, and 0.5% (v/v) penicillin/streptomycin], switched to low K ϩ (Eagle's basal medium, 5 mM KCl, 2 mM glutamine, and 0.5% penicillin/streptomycin) at day 4, treated with additives for the indicated time points, and processed for the specific assays described below.…”
Section: -Phenyl-1(4 H)-benzopyran-4-one (Ly294002) (Ly) Rabbit Polmentioning
confidence: 99%
“…Western blot analysis was performed as described previously (Subramaniam et al, 2003). Densitometric quantification of Western blots was done using NIH Image (version 1.61) software.…”
Section: -Phenyl-1(4 H)-benzopyran-4-one (Ly294002) (Ly) Rabbit Polmentioning
confidence: 99%